Analysis of Key Factors for Improved Customer Experience, Engagement, and Loyalty in the E-Commerce Industry in Indonesia - Antonius Felix; Glisina Dwinoor Rembulan (Aptisi Transactions On Technopreneurship (ATT), 2023)
In Indonesia's rapidly growing e-commerce industry, customer experience, engagement, and loyalty are pivotal variables for business success and sustainability. By addressing gaps in understanding these critical factors to enhance positive customer experiences, optimize engagement levels, and fortify customer loyalty. This research aims to identify key factors influencing customer experience, engagement, and loyalty in Indonesia's e-commerce industry, hence resulting in practical implementation recommendations for companies interested in developing an e-commerce platform or as a reference for future research. This study employs an explanatory qualitative approach to explore the intricate relationship between customer experience, engagement, and loyalty in the dynamic landscape of the e-commerce industry. Data is gathered from five prominent e-commerce platforms in Indonesia. The qualitative analysis delves into the narratives of these respondents, uncovering rich insights into their perceptions. Recommendations to bridge these gaps include implementing live chat with sellers, elevating personalized content and recommendations, prioritizing responsiveness and page loading speed, emphasizing security in online shopping, and amplifying personalized content and recommendations during customer engagement. Adopting these strategies, e-commerce companies can deliver more gratifying customer experiences, elevate engagement, and strengthen loyalty, thus establishing a competitive advantage in this dynamic market and fostering sustainable business growth. The research identifies factors impacting customer experience, engagement, and loyalty in e-commerce. Key factors for a positive experience include discounts, product quality, user interface, and customer support. Addressing gaps between factors and expectations can enhance satisfaction and loyalty. Recommendations include live chat, personalization, speed, security, and content improvement for a competitive advantage and sustainable growth. The recommendations for future research include conducting a comparative analysis, undertaking a longitudinal study, testing implementation strategies, and measuring long-term loyalty effects.